The Model of Value of a Media Product - Pitoňáková, Slavka (Communication Today, 2023)
The aim of the study is to present a theoretical model that describes the value of a media product while presenting a synergy of economic, content, social, cultural and other factors. This synergy brings an expanded perception of the value of a media product not only as a commodifiable and consumable product, but it also enriches the value of a media product with new perspectives and insights. At the same time, the model is applicable to all types of media products (print, audio and audiovisual, online, offline media products). Due to the limited amount of available literature that is directly related to the presented topic and as a result of the impossibility of following a relevant theory that exists, exploratory research (focused on new features) was conducted, which was followed by a qualitative research method – Grounded Theory. The new model of the value of media product that is presented is followed by defining new concepts (these concepts have not been used so far) that are related to media products with a high cultural value – heritage media products (media products focused on the topic of cultural heritage) and total heritage media products (heritage media products that are cultural heritage in themselves).